Peluang Investasi Pada Kawasan Wisata Taman Nasional Tanjung Puting (TNTP) Di Kabupaten Kotawaringin Barat Provinsi Kalimantan Tengah Dengan Sistem Built Operate Transfer (BOT) - Laras Mitra Parayogi; M. Ruslin Anwar; Alwafi Pujiraharjo (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2014)
The development of the tourism sector in Indonesia is one of the potential investment is promising. But not all potential can be developed .Such is the case with the tourism sector in Kotawaringin Barat exspecially is the Tanjung Puting National Park (TNTP). One of the barriers are is the limitation of funds and Government resources in developing this sector. Therefore required partnership with the private sector is a Built Operate Transfer (BOT). The purpose of this research are: (1) to know the means of tourism is needed at the time of a visit in the area of tourism, (2) to test the feasibility of financial investments on the TNTP without a BOT system, (3) to test the feasibility of financial investments on the TNTP without a BOT system. The research method used questionnaire for tourist at TNTP, and count financial feasibility with Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Profitability Index (PI), and descriptive statistical analysis methods.Survey at TNTP location to know real condition and interview with employee Balai Taman Nasional Tanjung Putting. The result of this research is that the facility is needed, campground cottage - inn, restaurant, boat kelotok, audio visual room, trackking area, gift shop, health clinic, and investment in the area of TNTP judged worth doing with BOT for maximum concession periode 18 years. If investment more than 18 years, prefer doing without BOT.Â